Research-Practice Partnerships in Education: Benefits for Researchers and Practitioners - Brown, Barbara (Alberta Journal of Educational Research, 2021)
The purpose of this research was to study how researchers and practitioners from universities and school authorities in Alberta, Canada, lead eleven research partnership projects, shared work and learning responsibilities, as well as understood their common challenges. Project leaders (N = 38) revealed their perceptions of the research partnership through an online survey and semi-structured interviews. Practitioners indicated advantages to partnering such as access to research expertise and data analysis tools in addition to deepening their research skills for educational decision making. Researchers outlined three benefits to the partnership: having access to research sites, learning more about current issues in schools, and developing relationships with practitioners. The researchers explained that these relationships would facilitate their ability to complete future research and conduct knowledge mobilization activities that would reach professional and academic audiences. Both researchers and participants identified challenges, such as time, communications, reporting requirements, and unforeseen circumstances while engaging in these research partnerships. Key words: University-school partnerships; educational partnerships; researcher-practitioner partnership; knowledge mobilization; case study L'objectif de cette recherche était d'étudier comment les chercheurs et les praticiens des universités et des autorités scolaires de l'Alberta, au Canada, ont dirigé onze projets de partenariat de recherche, partagé les responsabilités de travail et d'apprentissage, et perçu leurs défis communs. Les chefs de projet (N = 38) ont révélé leurs perceptions du partenariat de recherche par le biais d'un sondage en ligne et d'entrevues semi-structurées. Les praticiens ont indiqué les avantages du partenariat, tels que l'accès à l'expertise en recherche et aux outils d'analyse des données, en plus de l'approfondissement de leurs compétences en recherche pour la prise de décision en matière d'éducation. Les chercheurs ont souligné trois avantages du partenariat : avoir accès à des sites de recherche, en apprendre davantage sur les problèmes actuels dans les écoles et développer des relations avec les praticiens. Les chercheurs ont expliqué que ces relations faciliteraient leur capacité à réaliser des recherches futures et à mener des activités de mobilisation des connaissances qui toucheraient des publics professionnels et universitaires. Les chercheurs et les participants ont identifié des défis, tels que le temps, les communications, les exigences en matière de rapports et les circonstances imprévues, dans le cadre de ces partenariats de recherche. Mots clés : partenariats université-école; partenariats éducatifs; partenariat chercheur-praticien; mobilisation des connaissances; étude de cas.